2016
DOI: 10.1042/bj20150812
|View full text |Cite
|
Sign up to set email alerts
|

A novel phosphorylation site at Ser130 adjacent to the pseudosubstrate domain contributes to the activation of protein kinase C-δ

Abstract: Protein kinase C-δ (PKCδ) is a signalling kinase that regulates many cellular responses. Although most studies focus on allosteric mechanisms that activate PKCδ at membranes, PKCδ also is controlled via multi-site phosphorylation [Gong et al. (2015) Mol. Cell. Biol. 35, 1727–1740]. The present study uses MS-based methods to identify PKCδ phosphorylation at Thr50 and Ser645 (in resting and PMA-treated cardiomyocytes) as well as Thr37, Thr38, Ser130, Thr164, Thr211, Thr215, Ser218, Thr295, Ser299 and Thr656 (as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…The S645 is considered a priming phosphorylation site, and it has been suggested that this modification converts PKCδ to its mature form [28,42,43]. There was no difference in non-specific PKCδ staining.…”
Section: Hyp Light-independent Effects On the Distribution And Phomentioning
confidence: 98%
“…The S645 is considered a priming phosphorylation site, and it has been suggested that this modification converts PKCδ to its mature form [28,42,43]. There was no difference in non-specific PKCδ staining.…”
Section: Hyp Light-independent Effects On the Distribution And Phomentioning
confidence: 98%
“…Notably, Src-dependent phosphorylation at positions in the regulatory moiety, including the C2 domain, drives PKCδ into the nucleus, where it can be cleaved by caspases to commit to an irreversible activation (Humphries et al 2008). Additionally, this isozyme can be converted to a constitutively active enzyme following oxidative stress-induced phosphorylation of Tyr311 in the hinge region, forming a docking site for its C2 domain: interaction between the hinge and C2 not only disrupts autoinhibitory constraints, but promotes the dephosphorylation of Ser357 in the kinase domain, a residue whose phosphorylation state tunes selectivity between Ser and Thr (Gong et al 2016). Phosphorylation sites immediately preceding the pseudosubstrate of PKCδ have also been identified and shown to enhance lipid-independent activity (Gong et al 2016).…”
Section: Pkc Family and Regulationmentioning
confidence: 99%
“…Additionally, this isozyme can be converted to a constitutively active enzyme following oxidative stress-induced phosphorylation of Tyr311 in the hinge region, forming a docking site for its C2 domain: interaction between the hinge and C2 not only disrupts autoinhibitory constraints, but promotes the dephosphorylation of Ser357 in the kinase domain, a residue whose phosphorylation state tunes selectivity between Ser and Thr (Gong et al 2016). Phosphorylation sites immediately preceding the pseudosubstrate of PKCδ have also been identified and shown to enhance lipid-independent activity (Gong et al 2016). Additionally, PKCβII has been shown to autophosphorylate at sites preceding its pseudosubstrate (Flint et al 1990), suggesting a general mechanism for PKC isozymes to sustain signaling.…”
Section: Pkc Family and Regulationmentioning
confidence: 99%
“…Interestingly, the alignment between IRF3 and IRF9 revealed that the IRF9 ancestral state Ser129 can be aligned to the IRF3 Ser123. In Eukaryotes, serine (S), threonine (T), and tyrosine (Y) residues are the most commonly used phosphorylation sites [ 26 , 37 , 38 ]. Through the linker region phosphorylation, the EBV-encoded kinase, BGLF4, can down-regulate the IRF3 transactivation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%